COVID-19 impact on teleactivities: Role of built environment and implications for mobility. (April 2022) - Mouratidis, Kostas; Peters, Sebastian
Highlights: Significant growth in most teleactivities (remote online activities) due to COVID-19. Telework, online learning, telehealth, and virtual meetings increased during COVID-19. Neighborhood density associated with more frequent telework and virtual meetings with friends and family during COVID-19. More local facilities associated with more frequent online learning during COVID-19. Short and long-term implications for mobility are discussed. Abstract: This paper presents new evidence on changes in a broad range of teleactivities due to the Coronavirus disease (COVID-19) pandemic and investigates how the built environment relates to these changes. The paper relies on survey and geospatial data from Oslo and its surrounding Viken region in Norway. Findings suggest that most teleactivities increased due to COVID-19. Telework, teleconferencing, online learning, telehealth, and virtual meetings with friends and family all increased during COVID-19 compared to the pre-COVID-19 period. The next step in the analysis examined relationships between built environment characteristics and teleactivities before and during COVID-19. Telework and virtual meetings increased to a greater extent in denser neighborhoods than in lower-density neighborhoods. A larger increase in online learning was associated with lower neighborhood density, lower accessibility to public transport, and more local facilities. Numerous local facilities were associated with more frequent telework and virtual meetings both before and during COVID-19. The substantial COVID-19-induced increase in teleactivities found in the study highlights the potential of information and communications technology (ICT) for replacing travel for various activities.